Green Finance and Low-Carbon Transformation: The Dual Mediation of Cost Optimization and Technological Innovation under Market Demand Moderation - Zhou, Libin; Li, Lingling; Abbasi, Ayesha Zaheer; Ahmad, Wasim (International Journal of Energy Economics and Policy, 2025)
This study explores how green finance drives the development of green and low-carbon enterprises in China and examines the moderating role of green market demand. Using quantitative methods, data were collected from 404 valid questionnaires covering industrial enterprises of varying sizes, regions, and years of establishment. Structural equation modeling and artificial neural network analysis were employed to test the proposed framework. The findings reveal that green finance significantly supports low-carbon transformation by enabling sustainable practices. Two key mediators—optimization of financing costs and low-carbon technological innovation—play crucial roles in this process. However, increased green market demand negatively moderates the effect of financing cost optimization, while positively enhancing the impact of technological innovation. These results highlight the dual moderating effects of market demand. The study contributes by constructing a hybrid model that integrates green finance mechanisms with low-carbon enterprise development and provides empirical insights based on Chinese industrial data. It underscores the importance of tailoring green finance policies to varying market conditions. Future research may expand on these findings by examining how green finance operates in different industrial contexts or market structures.